Effects of yoga on patients with chronic nonspecific neck pain: A PRISMA systematic review and meta-analysis - Li, Yunxia (Medicine (Baltimore), 2019)
BACKGROUND: Chronic nonspecific neck pain (CNNP) has a high prevalence and is more common among younger people. Clinical practice suggests that yoga is effective in relieving chronic pain. OBJECTIVES: This meta-analysis aimed to quantitatively summarize the efficacy of yoga for treating CNNP. DATA SOURCES: We searched for trials in the electronic databases from their inception to January 2019. English databases including PubMed, MEDLINE, Cochrane Library, Embase, Scopus, the Cochrane Central Register of Controlled Trials, and Ind Med; Chinese databases including China National Knowledge Infrastructure (CNKI), WanFang Database, and VIP Information. We also conducted a manual search of key journals and the reference lists of eligible papers to identify any potentially relevant studies we may have missed. We placed no limitations on language or date of publication. STUDY ELIGIBILITY CRITERIA: We included only randomized controlled trials (RCTs) and q-RCTs evaluating the effects of yoga on patients with CNNP. The primary outcomes for this review were pain and disability, and the secondary outcomes were cervical range of motion (CROM), quality of life (QoL), and mood. PARTICIPANTS AND INTERVENTIONS: Trails that examined the clinical outcomes of yoga intervention in adults with CNNP compared with those of other therapies except yoga (e.g., exercise, pilates, usual care, et al) were included. STUDY APPRAISAL AND SYNTHESIS METHODS: Cochrane risk-of-bias criteria were used to assess the methodological quality, and RevMan 5.3 software was used to conduct the meta-analysis. RESULTS: A total of 10 trials (n = 686) comparing yoga and interventions other than yoga were included in the meta-analysis. The results show that yoga had a positive effects on neck pain intensity (total effect: SMD = −1.13, 95% CI [−1.60, −0.66], Z = 4.75, P < .00001), neck pain-related functional disability (total effect: SMD = −0.92, 95% CI [−1.38, −0.47], Z = 3.95, P < .0001), CROM (total effect: SMD = 1.22, 95% CI [0.87, 1.57], Z = 6.83, P < .00001), QoL (total effect: MD = 3.46, 95% CI [0.75, 6.16], Z = 2.51, P = .01), and mood (total effect: SMD = −0.61, 95% CI [−0.95, −0.27], Z = 3.53, P = .0004). CONCLUSIONS AND IMPLICATIONS OF KEY FINDINGS: It was difficult to make a comprehensive summary of all the evidence due to the different session and duration of the yoga interventions, and the different outcome measurement tools in the study, we draw a very cautious conclusion that yoga can relieve neck pain intensity, improve pain-related function disability, increase CROM, improve QoL, and boost mood. This suggests that yoga might be an important alternative in the treatment of CNNP. SYSTEMATIC REVIEW REGISTRATION NUMBER: Details of the protocol for this systematic review and meta-analysis were registered on PROSPERO and can be accessed at www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42018108992.